Re-contextualization of Discretized Fuzzy Cyber-Risk Functional Arguments with Fuzzy Polynomials - Boateng, Ezer Osei Yeboah (International Journal of Computer Sciences and Engineering, 2016)
Re-contextualization is basically a transformative process of reframing a system structure to assume that of another system. It extracts texts, symbols, signs, artefacts, or meanings from its original structure to assume another structure in context. The concept is applied in abstract and quantitative fuzziness to resolve and re-interpret discrete fuzzy function by assuming fuzzy polynomial structure. This study is premised upon the fuzziness in relationships exhibited by cyber-security vulnerabilities and threat constructs as fuzzy functions. The evaluation of discrete fuzzy functions based on arbitrary equidistant computations render the solution indeterminate. However, re-contextualizing the cyber-risk function into a fuzzy polynomial simplifies the solution and depicts its functional nature for real world applications. Numerical examples are used to illustrate the concept by the Ranking method.